Comparison of the results of bioelectric impedance analysis (BIA) and the anthropometry (Drinkwater-Ross & Parizkova) method in young elite athletes - Fügedi, B.; Szakaly, Z.; Suszter, L. (Journal of Physical Education and Sport, 2023)
BACKGROUND: The literature provides relatively few and incomplete studies on comparisons of body composition measurement procedures, especially when related to sport experience, gender and age. The purpose of this study was to compare and contrast the applicability of the bioelectric impedance (BIA) and the four-component anthropometry (Drinkwater-Ross) methods among young athletes. METHODS: 142 school-agedcompetitive athletes (nmale=71; nfemale=71, Mage=11.72±2.33) from a suburb in Hungary participated in the study. Data collection included standard Drinkwater-Ross anthropometric fractionation (bone mass, muscle and fat mass, and residual mass, estimated by equations) and bioelectrical impedance analysis with measured muscle mass (SMM_Inbody) and body fat percentage (PBF%Inbody) methods. In order to better understand the higher standard correlations of the methods, Parízkova percentage of body fat (Parízkova BF%) was also included in the analysis. Data analysis was performed by gender and age range. RESULTS: According to the data, it seems that the muscle mass estimated by BIA (SMM Inbody) is higher than the Drinkwater-Ross estimation (eMM) both in males and females and in each age-group. Also, muscle mass is overestimated, meanwhile body fat% (PBF%Inbody) is underestimated by BIA compared to Parízkova BF%. However, our results show significant correlations (0.6<r>0.9, p<.001) between estimated fat mass and muscle mass in all cases (eMM, eFM); similarly, the estimated body fat percentages in all cases were strongly correlated (Parízkova BF% and PBF%Inbody). CONCLUSIONS: Correlational analyses proved that estimation of body fat mass, muscle mass, and percentage of body fat by BIA measurement are closely associated with both Drinkwater-Ross anthropometric fractionation and Parízkova. Our findings suggest that the (BIA) predictive performance is equally appropriate as other reference techniques (e.g. Drinkwater-Ross, Parízkova) in the case of young athletes. Consequently, both the device (bioelectrical impedance device) and the ease of use of the results make for a truly user-friendly and scientifically supported procedure.